EpCAM-positive disseminated cancer cells in bone marrow impact on survival of early-stage NSCLC patients - Mederer, Tobias; Elsner, Felix; Robold, Tobias; Großer, Christian; Neu, Reiner; Ried, Michael; Bleicher, Sabine; Schamberger, Thomas; Blochberger, Isabell; Hofmann, Hans Stefan; Klein, Christoph A. (Lung Cancer, 2022)
Introduction: Detection of disseminated cancer cells (DCC) in bone marrow (BM) of patients with early-stage NSCLC has been associated with poor outcome. However, the phenotype, and hence relevant therapy targets, of DCCs in BM are unknown. We therefore compared a classical pan-Cytokeratin (CK) antibody for DCC detection with an anti-EpCAM antibody that may also detect more stem-like cells and tested whether assay positivity impacts on the survival of NSCLC patients. Materials and methods: We prospectively collected BM aspirates from 104 non-metastasized NSCLC patients that underwent potentially curative tumor resection from 2011 to 2016 at the Department of Thoracic Surgery of the University Hospital and Hospital Barmherzige Brüder in Regensburg. DCCs were detected by staining with the pan anti-CK antibody A45-B/B3 and the anti-EpCAM antibody HEA-125. We analyzed the association between detection of DCCs and clinicopathological characteristic and patient outcome. Results: CK + and EpCAM + DCCs were detected in 45.2% and 52.9% of patients, respectively. Correlation between the two markers was low and neither of them was associated with sex, age, histology, T or N classification, resection status, grading or smoking habit. No significant association with tumor specific survival (TSS) and progression-free survival (PFS) was observed in patients with CK + DCCs. In contrast, detection of EpCAM + DCCs significantly correlated with reduced PFS (P = 0.017) and TSS (P = 0.017) and remained an independent prognostic variable for PFS and TSS upon multivariate testing (hazard ratio: 7.506 and 3.551, respectively). Detection of EpCAM + DCCs was the only prognostic marker for PFS. Conclusions: EpCAM+, but not CK + DCCs in BM predict reduced PFS and TSS. This finding suggests that EpCAM + DCCs in the BM comprise metastatic founder cells necessitating their in-depth molecular analysis for detection of novel therapy targets.
CRIS-Team Scopus Importer:2022-04-29
Keywords: Biomarker; Bone marrow; Disseminated cancer cell; Early dissemination; Lung cancer; Metastasis